Neural drive and motor unit characteristics after anterior cruciate ligament reconstruction: implications for quadriceps weakness - Sherman, David A.; Rush, Justin; Stock, Matt S.; D. Ingersoll, Christopher; E. Norte, Grant (PeerJ, 2023)
Purpose The purpose of this investigation was to compare the quality of neural drive and recruited quadriceps motor units’ (MU) action potential amplitude (MUAPAMP) and discharge rate (mean firing rate (MFR)) relative to recruitment threshold (RT) between individuals with anterior cruciate ligament reconstruction (ACLR) and controls. Methods Fourteen individuals with ACLR and 13 matched controls performed trapezoidal knee extensor contractions at 30%, 50%, 70%, and 100% of their maximal voluntary isometric contraction (MVIC). Decomposition electromyography (dEMG) and torque were recorded concurrently. The Hoffmann reflex (H-reflex) and central activation ratio (CAR) were acquired bilaterally to detail the proportion of MU pool available and volitionally activated. We examined MUAPAMP-RT and MFR-RT relationships with linear regression and extracted the regression line slope, y-intercept, and RT range for each contraction. Linear mixed effect modelling used to analyze the effect of group and limb on regression line slope and RT range. Results Individuals with ACLR demonstrated lower MVIC torque in the involved limb compared to uninvolved limb. There were no differences in H-reflex or CAR between groups or limbs. The ACLR involved limb demonstrated smaller mass-normalized RT range and slower MU firing rates at high contraction intensities (70% and 100% MVIC) compared to uninvolved and control limbs. The ACLR involved limb also demonstrated larger MU action potentials in the VM compared to the contralateral limb. These differences were largely attenuated with relative RT normalization. Conclusions These results suggest that persistent strength deficits following ACLR may be attributable to a diminished quadriceps motor neuron pool and inability to upregulate the firing rate of recruited MUs.
Keywords: Anterior cruciate ligament; Quadriceps weakness; Motor neuron pool; Motor unit; Voluntary activation; rehabilitation